2008
DOI: 10.1007/s00467-007-0664-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of mizoribine as a rescue drug for steroid-resistant pediatric IgA nephropathy

Abstract: Recent clinical trials have shown a beneficial effect of mizoribine (Miz), an immunosuppressive drug, in the treatment of new-onset pediatric IgA nephropathy (IgAN). In this study, we evaluated the efficacy of Miz treatment in three children with established steroid-resistant IgAN. The patients had IgAN featuring persistent proteinuria and diffuse mesangial proliferation and had failed to respond to 2 years of treatment with prednisolone. Based upon the second biopsy results, patients were given methylpredniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Cases of steroid-resistant disease are treated with additional immunosuppressant agents. For example, mizoribine (MZR) is used as a rescue drug in steroid-resistant IgA nephropathy [10,11], but little is known of any potential effects of MZR upon macrophage activation.…”
Section: Introductionmentioning
confidence: 99%
“…Cases of steroid-resistant disease are treated with additional immunosuppressant agents. For example, mizoribine (MZR) is used as a rescue drug in steroid-resistant IgA nephropathy [10,11], but little is known of any potential effects of MZR upon macrophage activation.…”
Section: Introductionmentioning
confidence: 99%
“…This may, in turn, lead to suppression of the activity of 3 1-integrin, which is known to play a role in the development of interstitial fibrosis. Indeed, in a clinical setting, it has also been reported that posttreatment renal biopsy specimen from patients with severe IgA nephropathy treated with MZR, showed marked attenuation of glomerular and interstitial lesions, and significantly reduced the number of activated macropharges, associated with the expression of 14-3-3 proteins and HSP60, which are known to be MZR-binding proteins, in the inflamed glomerular cells (Ikezumi et al, 2008). Thus, it is speculated that MZR may bind directly to inflamed glomerular cells and prevent progressive damage by suppressing activated macrophages and intrinsic renal cells.…”
Section: Mizoribine a Selective Inhibitor Of Inosine Monophosphate Dmentioning
confidence: 94%
“…This low clinical toxicity is an important advantage of MZR-P treatment, especially for long-term treatment of young patients. Besides its immunosuppressive effects, MZR has recently been reported to suppress the progression of histologic chronicity in selected patients with lupus nephritis and IgA nephropathy (Kawasaki et al, 2004;Tanaka et al, 2007b and c;Ikezumi et al, 2008). Moreover, MZR has been reported to attenuate tubulointerstitial fibrosis in a dosedependent manner in rat models of unilateral ureteral obstruction, non-insulin-dependent diabetes and peritoneal fibrosis via suppression of macrophage infiltration of the interstitium (Sato et al, 2001;Kikuchi et al, 2005;Takahashi et al, 2009).…”
Section: Mizoribine a Selective Inhibitor Of Inosine Monophosphate Dmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnosis of IgAN with pathological features of membranoproliferative glomerulonephritis (MPGN) type I was made. Combination therapy was started as reported previously, with modifications [7][8][9]. The modified combination therapy consisted of prednisolone, mizoribine, heparin-warfarin, urokinase, dipyridamole, and candesartan cilexetil.…”
Section: Case Reportmentioning
confidence: 99%